Analysis of Behavioral Indicators as a Measure of Satiation. (March 2017) - Scalzo, Rachel; Davis, Tonya N.
Providing noncontingent access to a stimulus until an individual displays behavioral indicators of satiation has been used to determine when an abolishing operation is in effect, but there has been variation in its application in the literature. Four males diagnosed with autism spectrum disorder with tangibly maintained challenging behavior participated in this study. Individualized behavioral indicators were identified and verified to determine when each participant was finished playing with his/her preferred item. Three presession conditions were manipulated including restricted access to the tangible stimulus for 30 min, access to the tangible stimulus until the display of one behavioral indicator, and access to the tangible stimulus until the display of three behavioral indicators. Each presession condition was followed by a tangible condition of the functional analysis to measure challenging behavior. Results indicated that presession access to a tangible stimulus until the display of three behavioral indicators produced a greater abative effect on challenging behavior than one behavioral indicator.